Business and financial information integration and voluntary management earnings forecasts - Jing Huang; Zipeng Mei; Zhe Li (China Journal of Accounting Research, 2020)
In this study, the impact of business and financial information integration (BFII) on the voluntary management earnings forecasts (VMEFs) of listed firms in China between 2008 and 2018 is investigated. Drawing on litigation cost and ability signaling theories, we find that the adoption of BFII encourages top managers to disclose VMEFs. BFII firms are identified through the textual analysis of management discussion and analysis (MD&A) reports, and the empirical results indicate that BFII firms have a higher probability and frequency of issuing VMEFs than non-BFII firms. The results remain robust after we identify causality by applying a propensity score matching and difference-in-differences (PSM-DID) test and use an alternate measure of BFII. Further tests show that BFII firms issue more accurate VMEFs and are able to issue them at an earlier stage. We also find that the positive relationship between BFII and VMEFs is weakened if the media expresses concern about the uncertainty of BFII adoption.
Keywords: G30; M40; M51; 650; Business and financial information integration; Management discussion and analysis (MD&A); Media coverage; Textual analysis; Voluntary management earnings forecasts (VMEF)